Understanding Family-Level Effects of Adult Chronic Disease Management Programs: Perceived Influences of Behavior Change on Adolescent Family Members' Health Behaviors Among Low-Income African Americans With Uncontrolled Hypertensions - Thornton, Rachel L. J.; Yang, Tracy J.; Ephraim, Patti L.; Boulware, L. Ebony; Cooper, Lisa A. (Frontiers in Pediatrics, 2019)
Background: Despite improvements in cardiovascular disease (CVD) prevention and treatment, low-income African Americans experience disparities in CVD-related morbidity and mortality. Childhood obesity disparities and poor diet and physical activity behaviors contribute to CVD disparities throughout the life course. Given the potential for intergenerational transmission of CVD risk, it is important to determine whether adult disease management interventions could be modified to achieve family-level benefits and improve primary prevention among high-risk youth. Objective: To explore mechanisms by which African-American adults’ (referred to as index patients) participation in a hypertension disease management trial influence adolescent family members’ (referred to as teens) lifestyle behaviors. Design/Methods: The study recruited index patients from the Achieving blood pressure Control Together (ACT) study who reported living with a teen ages 12-17 years old. Index patients and teens were recruited for in-depth interviews and were asked about any family-level changes to diet and physical activity behaviors during or after participation in the ACT study. If family-level changes were described, index patients and teens were asked whether role modeling, changes in the home food environment, meal preparation, and family functioning contributed to these changes. Thematic content analysis of transcribed interviews identified a priori and emergent themes. Results: Eleven index patients and their teens participated in in-depth interviews. Index patients and teens both described changes to the home food environment and meal preparation. Role modeling was salient to index patients, particularly regarding healthy eating behaviors. Changes in family functioning due to study participation were not endorsed by index patients or teens. Emergent themes included teen care-taking of index patients and varying perceptions by index patients of their influence on teens’ health behaviors. Conclusions: Our findings suggest that disease management interventions directed at high-risk adult populations may influence adolescent family members’ health behaviors. We find support for the hypotheses that role modeling and changes to the home food environment are mechanisms by which family-level health behavior change occurs. Teens’ roles as caretakers for index patients emerged as another potential mechanism. Future research should explore these mechanisms and ways to leverage disease management to support both adult and adolescent health behavior change.